Periodontitis pada lansia - Ananda Putri, Salsabilla; Astuti, Luki; Nauli Komala, Olivia (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Periodontitis is one of the most common periodontal diseases worldwide and has a high prevalence among the elderly. This disease is caused by microorganisms in dental plaque, which lead to inflammation and damage to the supporting tissues of the teeth. In Indonesia, the prevalence of periodontitis among the elderly reaches 66%, higher than in other age groups. The elderly are more susceptible to periodontitis due to a decline in immune system function, systemic diseases such as diabetes, and suboptimal oral hygiene. This condition is exacerbated by dry mouth due to medication use, such as xerostomia. The main manifestations of periodontitis in the elderly include gingival inflammation, formation of periodontal pockets, alveolar bone loss, and tooth mobility. Periodontitis significantly impacts the quality of life of the elderly, including tooth loss, which affects their ability to chew, eating patterns, and speech. Additionally, periodontitis is associated with increased systemic inflammation, which can affect overall health conditions such as cardiovascular diseases, nutritional status, and physical function.